Guaran-based biodegradable and conducting interpenetrating polymer network composite hydrogels for adsorptive removal of methylene blue dye. (December 2015) - Sharma, Reena; Kalia, Susheel; Kaith, Balbir S.; Pathania, Deepak; Kumar, Amit; Thakur, Pankaj
Abstract: Microwave initiated grafting of itaconic acid was carried out on guaran polysaccharide to get a crosslinked network of guaran–itaconic acid. Different reaction parameters were optimized for the graft copolymerization of itaconic acid on guaran to get the candidate polymer with maximum percentage swelling. Conducting interpenetrating polymer network (IPN) was prepared by aniline absorption in the semi-IPN network by two-step aqueous polymerization. Crosslinked structure was characterized by Fourier transform infra-red spectroscopy (FTIR), thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). Biodegradation of synthesized hydrogels was studied by soil burial and composting methods and monitored by FTIR and SEM techniques. Conducting interpenetrating polymer network composite hydrogels were studied for the adsorptive removal of methylene blue dye. Pseudo first and pseudo second order kinetics models were used to describe the adsorption kinetics of dye removal.